2011
DOI: 10.1016/j.ijom.2011.07.125
|View full text |Cite
|
Sign up to set email alerts
|

Safety of colorado microdissection needle (Stryker) for skin opening in craniomaxillofacial surgery

Abstract: Purpose Diathermy is used widely in surgical procedures, mainly for subcutaneous and deeper layers dissection. The use on craniomaxillofacial skin has been precluded by the fear of scar formation, alopecia and wound dehiscence. The aim of this study was to clinically evaluate the safety of Colorado Microdissection needle (Stryker) for skin opening in craniomaxillofacial surgery. Materials and Methods 117 skin incisions for craniomaxillofacial procedures were performed using the Stryker Colorado microdissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…15,16 Similar to the results reported in the general surgery literature, Sheikh 15 found that using microneedle electrocautery for 117 neurosurgical procedures, including 85 cranial incisions, resulted in decreased blood loss and incision time. He recommends the use of microneedle electrocautery not only for pediatric cases in which strict control of hemostasis is particularly important but also for all neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…15,16 Similar to the results reported in the general surgery literature, Sheikh 15 found that using microneedle electrocautery for 117 neurosurgical procedures, including 85 cranial incisions, resulted in decreased blood loss and incision time. He recommends the use of microneedle electrocautery not only for pediatric cases in which strict control of hemostasis is particularly important but also for all neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 54%
“…No significant differences in wound complication rates were reported for incisions made with the 2 modalities for head and neck cancer: craniomaxillofacial surgery and neurosurgery. 6,[15][16][17] This is especially important for the hair-bearing scalp because wound-healing problems often result in scar widening with clinically evident alopecia. Sharma 16 evaluated the use of a microdissection electrocautery needle in making 117 incisions in craniomaxillofacial surgery, including 10 scalp incisions, and found no increased risk from the use of electrocautery in wound infection or alopecia rates.…”
Section: Discussionmentioning
confidence: 99%
“…The general surgical use of electrocautery had been mainly reserved for incising and dissecting the subcutaneous tissue and deeper layers. The use of the electrocautery scalpel to open skin has been rejected or reserved in past for fear of delayed wound healing or infection [4]. Currently there is enough literature and evidence to support favorable use of electro-cautery as a complete or partial substitution to cold steel, in terms of operative blood loss, post-operative pain and surgical scar [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the electrocautery scalpel to open skin has been rejected or reserved in past for fear of delayed wound healing or infection [4]. Currently there is enough literature and evidence to support favorable use of electro-cautery as a complete or partial substitution to cold steel, in terms of operative blood loss, post-operative pain and surgical scar [4][5][6]. The electrocautery knife has been used widely by general surgeons to create abdominal and thoracic incisions, with excellent results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation